AHP Analysis to Set a Direction for Rural Convergence Industry Startup Education - B. Song, I.; S. Park, M. (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study 34 subjects consisting of experts in the Gyeongnam region, scholars, entrepreneurs and those wishing to become entrepreneurs to conduct an analysis on the relative importance of factors in rural convergence industry startup education to set a direction for such education programs.Methods/Statistical analysis: This study, we analyzed using AHP(Analytic Hierarchy Process).Findings: The relative importance or priority of areas in rural convergence industry startup education were in descending order, â€˜foundation of startupâ€™, â€˜startup preparation and environment analysisâ€™, â€˜entrepreneurshipâ€™, â€˜startup management strategyâ€™, â€˜startup specialized programâ€™ and â€˜startup practiceâ€™. The ranking for factors were in descending order, startup, environment analysis, startup item, entrepreneurship, startup trend, startup plan, marketing, startup financing and M&A, culture and organizational growth management, agriculture venture, creativity, finance accounting and startup finance, legal affairs and system consulting, startup management strategy, agriculture products marketing, field practice, innovative thinking, consulting, business model, agriculture venture related laws, technology commercialization, agriculture corporation, agriculture venture case, business plan, 6th industry and smart farm.Improvements/Applications: This study may be used in decision-making regarding where to place the relative importance and priority in rural convergence industry startup education as it sought to conclude implications for the future direction of lifelong education and rural convergence industry startup education programs.Â